2023
DOI: 10.3390/healthcare11020155
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Bawazir et al. Nutritional Knowledge and Attitudes among Physician Interns Graduated from King Abdul-Aziz University, Jeddah, Saudi Arabia. Healthcare 2022, 10, 1788

Abstract: In the original publication [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Studies on the perceptions of undergraduate medical students toward Integrated Management of Childhood Illness (IMCI) Preservice Education have shown that five-year-old medical students need more knowledge regarding IMNCIs [26]. Another cross-sectional study aimed at assessing the nutritional knowledge and attitudes of medical students at King Abdul-Aziz University, Jeddah, Saudi Arabia, demonstrated that participants needed better knowledge regarding malnutrition in children [27]. These findings indicate that medical students struggle to retain critical yet factual concepts related to pediatric health, which will ultimately affect their performance in their clinical rotations and future training.…”
Section: Table 1 Comparison Of Participant Characteristics and Test R...mentioning
confidence: 99%
“…Studies on the perceptions of undergraduate medical students toward Integrated Management of Childhood Illness (IMCI) Preservice Education have shown that five-year-old medical students need more knowledge regarding IMNCIs [26]. Another cross-sectional study aimed at assessing the nutritional knowledge and attitudes of medical students at King Abdul-Aziz University, Jeddah, Saudi Arabia, demonstrated that participants needed better knowledge regarding malnutrition in children [27]. These findings indicate that medical students struggle to retain critical yet factual concepts related to pediatric health, which will ultimately affect their performance in their clinical rotations and future training.…”
Section: Table 1 Comparison Of Participant Characteristics and Test R...mentioning
confidence: 99%